(x-2)/3=(x+7)/6

Simple and best practice solution for (x-2)/3=(x+7)/6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x-2)/3=(x+7)/6 equation:


x in (-oo:+oo)

(x-2)/3 = (x+7)/6 // - (x+7)/6

(x-2)/3-((x+7)/6) = 0

(x-2)/3+(-1*(x+7))/6 = 0

(6*(x-2))/(3*6)+(-1*3*(x+7))/(3*6) = 0

6*(x-2)-1*3*(x+7) = 0

3*x-33 = 0

(3*x-33)/(3*6) = 0

(3*x-33)/(3*6) = 0 // * 3*6

3*x-33 = 0

3*x-33 = 0 // + 33

3*x = 33 // : 3

x = 33/3

x = 11

x = 11

See similar equations:

| -5x+3(2)=-9 | | -5(-3+3y)+3y=-9 | | y-3x=2 | | -(-6x+z)+(y+4)=0 | | 1/2(5x-3)=8 | | 5-9x=3x-8x-27 | | 2(5)-13=y | | 3(5)+2(2(5)-13)=9 | | 8x^3-3x^2-36x+9=0 | | .50(5x-3)=8 | | (y-7)-(y+4)=4y | | 11x+5x=80 | | 3x+2(2x-13)=9 | | -7x-9=-93 | | Y=500+40x-x^2 | | (x+1)(x-4)= | | 17-4x/12=5 | | 20-6xn=10 | | 21/(y-8)=3 | | 2xn+4=6y | | 4(2x+3)=15x | | 7(d+2)=10(d+5) | | -10(s+4)=-100 | | 4b-3(2b-6)=3-(5b+9) | | 35+10=35 | | 3p=-48 | | 39+7=28 | | 8a-5-7a=3+5 | | 98=7t | | 18+3x=30 | | -7x+6x+3=0 | | (x-5)/8=-2 |

Equations solver categories